Trends of clandestine laboratories manufacturing methamphetamine in New Zealand between 2009–2021: Evolution, enforcement, legislative, and COVID‐19 effects. Issue 1 (21st October 2022) - Bogun, Ben; McKinnel, Megan; Russell, Matthew; Watson, Janine; Mayo, Erina; Marr, Brooke; Larsen, Annie; Craig, Jessica
Abstract: The most common method of domestic methamphetamine manufacture encountered in New Zealand is the hydrogen iodide (HI) reduction of pseudoephedrine/ephedrine. While the overall method used to manufacture methamphetamine has remained consistent, the processes and chemicals utilized have evolved. Understanding the reason for any changes to methamphetamine manufacturing trends can assist jurisdictions with predicting the potential effects of enforcement and legislative initiatives. This paper presents data and trends amassed from suspected clandestine laboratories, associated with the manufacture of methamphetamine, in New Zealand between 2009 and 2021, along with data on methamphetamine, pseudoephedrine, and ephedrine seizures at the border. The data have shown that clandestine manufacturers in New Zealand have evolved the methamphetamine manufacturing process over the years. These changes in trends can largely be attributed to various enforcement and legislative effects and the COVID‐19 pandemic response. Effects that enforcement, legislation, and the COVID‐19 pandemic response may have had on the precursors, chemicals and equipment encountered are discussed.